The Correlation Between Concept Mastery and Students Moral Reasoning Stage Through Socio Scientific Issue Approach on Human Reproduction System Material - Eva Sujiati; Baiq Sri Handayani; I Wayan Merta; Tri Ayu Lestari; I Putu Artayasa (Pascasarjana, Mataram University, 2021)
The aim of this study was to obtain empirical data regarding the relationship between the mastery of concept, and the stage of students’ moral reasoning. The research method used was correlational research with cluster random sampling technique. The population in this study were all senior high schools in the city of Mataram and the sample consisted of 171 class XII students from three public senior high schools in the city of Mataram. Data collection was carried out using a concept mastery test instrument in the form of multiple choice questions and a moral reasoning stage test using a questionnaire on socio-scientific issues. The results of the research as a whole, it consisted of (1) Test of mastery of the material concept of the reproductive system of students in the less category with a percentage of 45%. (2) The moral reasoning test of students was categorized into the category of beginner reasoning stage with a percentage of 56% (3) The correlation test on concept mastery and moral reasoning stage used Spearman correlation and it showed that there was a significant relationship (r = 0835, = 0.000) with positive direction. This positive and significant relationship can be interpreted that the higher the mastery of the material concepts of the reproductive system of students, the better the stage of students’ moral reasoning.